2.60. Rozwiąż równania: (x – 1) ^ 2 – (x + 4) ^ 2 = – 2x + 1 1 b) (x + 5) ^ 2 – (x – 3) ^ 2 = x + 1 a) c) (x + 1) ^ 2 + (x – 3)(x + 3) – 2 = 2(x – 1) d) (2 – x)(2 + x) + (x + 3) ^ 2 = x – 7 e) (x + 3) ^ 2 – (4 – x)(4 + x) = 2 * (x – 1) ^ 2 + 1 (x – 5) ^ 2 – (x – 3) ^ 2 = 4(x – 2) g) (x – sqrt(3))(x – sqrt(3)) – (x + sqrt(3))(x + sqrt(3)) – sqrt(12) = 0 f) h) (x + 2sqrt(5)) ^ 2 + (x – 2sqrt(5)) ^ 2 = 46

2.60. Rozwiąż równania: (x – 1) ^ 2 – (x + 4) ^ 2 = – 2x + 1 1 b) (x + 5) ^ 2 – (x – 3) ^ 2 = x + 1 a) c) (x + 1) ^ 2 + (x – 3)(x + 3) – 2 = 2(x – 1) d) (2 – x)(2 + x) + (x + 3) ^ 2 = x – 7 e) (x + 3) ^ 2 – (4 – x)(4 + x) = 2 * (x – 1) ^ 2 + 1 (x – 5) ^ 2 – (x – 3) ^ 2 = 4(x – 2) g) (x – sqrt(3))(x – sqrt(3)) – (x + sqrt(3))(x + sqrt(3)) – sqrt(12) = 0 f) h) (x + 2sqrt(5)) ^ 2 + (x – 2sqrt(5)) ^ 2 = 46